Absorption spectral properties of Cu2+ ions in sodium potassium sulphate - Rama Kumar, R.; Reddy, C. V. Krishna; Venkata Reddy, B. C. (Ferroelectrics. Letters section, 1997)
This short note reports the results concerning electron paramagnetic resonance (EPR) and optical absorption spectra of Cu 2+ ions doped in sodium potassium sulphate both at 300K and 77K.